PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS MELALUI PEMBELAJARAN BERBANTUAN MACROMEDIA FLASH MX - Nasrullah, Anton; Dwiyanti, Widya (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2016)
Mathematical communication ability is an important ability that the students must possess. In this study, learning assisted with Macromedia flash MX was used to increase studentsâ mathematical communication ability. Aside from the use of software, the role of supporting tools in learning was also investigated. Subjects were 65 Vocational Schools (SMK) students divided into 32 students in control class (learning assisted with Macromedia flash MX) and 33 students in the experimental class (learning assisted with Macromedia flash MX and additional supporting tools, MFMX+). Mathematical communication ability was evaluated through written test. Results showed an increase in mathematical communication ability both in the control and experimental class, albeit to a different degree. Students in MFMX+ class showed a higher mathematical communication ability improvement compared to students in control class. Learning assisted with Macromedia flash MX improved mathematical communication ability and supporting tools maximize benefits that can be gained from the use of Macromedia flash MX.